+0  
 
-1
375
1
avatar+49 

Thank you

 Sep 15, 2017
edited by Guest  Sep 15, 2017
 #1
avatar+98173 
+1

z = 6 π x y      for  x

divide both sides by  6 π y

z / [ 6 π  y ]    = x

 

a(b − c)= d     for c  

divide both sides by a

b - c   = d / a    

Multiply both sides by  - 1

c - b  =  - d / a   

add b to both sides

c  = b -  [d / a]

 

 

d = 5x + 5y     for y

subtract 5x from both sides

d - 5x  = 5y

dibvide both sides by 5

[ d - 5x ] / 5    = y

 

A=h(a+b)/2    for b

multiply both sides by 2

2a  = h (a + b)

divide both sides by h

[2a ] / h   =  a  + b 

subtract a from both sides

[ 2a ] / h   - a   =  b

 

P=2(l+w)    for  l

divide both sides by 2

P / 2   =  l + w

subtract w from both sides

[P / 2]  - w    =    l

 

 

 

cool cool cool

 Sep 15, 2017

7 Online Users

avatar